2021
DOI: 10.1177/00912174211042695
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental health: Anxiety disorders among immigrants due to COVID-19 outbreak in South Korea

Abstract: Background The COVID-19 pandemic has affected various facets of health. While mental health became a major concern during the COVID-19 outbreak, the impact on the migrants’ mental health has still been neglected. The purpose of this study was to examine the COVID-19 outbreak's impact on the mental health of immigrants in South Korea. Methods A total number of 386 immigrants in South Korea participated in this quantitative cross-sectional study. The standardized e-questionnaire, including the General Anxiety Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Measures to contain the spread of the virus have involved lockdowns and mobility restrictions, while migrant essential workers have had to work in precarious working conditions with a high risk of infection due to limited health and safety protection measures ( 9 ). All of this appears to have been detrimental to migrants' mental health, both for those who have remained in destination countries ( 50 ) and for those who have been forced to return to their countries of origin ( 51 ). According to our results and the research on migrant health in general ( 52 , 53 ), mental health of migrant workers during COVID-19 seems to be of great interest to researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Measures to contain the spread of the virus have involved lockdowns and mobility restrictions, while migrant essential workers have had to work in precarious working conditions with a high risk of infection due to limited health and safety protection measures ( 9 ). All of this appears to have been detrimental to migrants' mental health, both for those who have remained in destination countries ( 50 ) and for those who have been forced to return to their countries of origin ( 51 ). According to our results and the research on migrant health in general ( 52 , 53 ), mental health of migrant workers during COVID-19 seems to be of great interest to researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The Immigration Services Agency of Japan reported that foreigners living in Japan had few connections with others outside of work (Immigration Services Agency of Japan, 2021b). A South Korean study conducted in October 2020 reported that immigrants who live alone have moderate-to-extreme anxiety symptoms when compared with those living with their families (Acharya et al, 2021). These findings indicate that connections with others, especially family members, are important for maintaining mental health among immigrants.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted during the COVID-19 pandemic have recently reported mental health crises among immigrants in the US (Galletly et al, 2021), Canada (Canada, 2020), Europe (Spiritus-Beerden et al, 2021), India (Choudhari, 2020), and South Korea (Acharya et al, 2021). However, the mental health status of immigrants in Japan during the COVID-19 epidemic remains unclear.…”
Section: Introduction1mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, young Koreans living in Japan have higher suicide mortality than their Japanese counterparts ( Gilmour et al, 2019 ). The pandemic likely disproportionately affected the mental health of immigrants: increased anxiety due to COVID-19 has been noted among Chinese women living in Japan ( Luo & Sato, 2021 ), international students in China ( Fakhar et al, 2020 ), and immigrants in South Korea ( Acharya et al, 2021 ). Furthermore, research in Japan has found that infant mortality and stillbirth rates are significantly higher for immigrant women than their Japanese counterparts, in part due to language barriers, relatively low socioeconomic status, and underutilization of health care services ( Kita et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%